Análise de alterações nucleares nas mucosas jugal, labial e lingual em indivíduos com epidermólise bolhosa residentes no Espírito Santo e correlações clínico-patológicas - Badaró, Rebeca Ferreira (2025)
Epidermolysis Bullosa (EB) is a severe genetic disorder characterized by the continuous formation of blisters on the skin and mucous membranes, potentially leading to significant structural alterations in the oral cavity. This study aimed to analyze nuclear aspects of cytotoxicity and mutagenicity in exfoliated cells from the buccal, labial, and lingual mucosa of patients with EB. Sociodemographic and clinical data were collected through physical examination and a standardized questionnaire. Exfoliated cells from the buccal, labial, and lingual mucosa were assessed for the frequency of micronuclei (MN), karyorrhexis (KR), karyolysis (KL), and pyknosis (PN). The Mann-Whitney and Kruskal-Wallis tests were used for statistical analysis. The study included 20 EB patients and 20 age- and sex-matched controls. A similar distribution was observed between males (40%) and females (60%), with a predominance of individuals ≤19 years old (65%). Quantitative analysis revealed a significant increase in KR and KL in EB patients compared to controls, particularly in the buccal (p=0.0002; p<0.0001) and labial mucosa (p=0.0005; p=0.0240). Additionally, MN frequency was higher in the EB group, especially in the buccal mucosa (p=0.0083). These findings indicate an increase in cytotoxic and mutagenic events in the oral mucosa of EB patients, suggesting a link between genomic instability and the disease. Cytological smear analysis may serve as a promising tool for the dental monitoring of these patients, particularly in severe cases